What a library means to a woman : Edith Wharton and the will to collect books - Liming, Sheila (University of Minnesota Press, 2020)
"This book makes a claim for the centrality of libraries to the mythos of self-making in late nineteenth and early twentieth-century American culture, focusing on Edith Wharton as its primary case in point. Wharton was never formally educated; rather, her private library collection, portions of which she inherited from her father, formed the basis of an education that would, in time, directly contribute to her success as a popular author"-- Provided by publisher.
Keywords: Wharton, Edith, -- 1862-1937 -- Criticism and interpretation.; Wharton, Edith, -- 1862-1937 -- Library.; Wharton, Edith, -- 1862-1937 -- Books and reading.; Wharton, Edith, -- 1862-1937; Libraries in literature.; Bibliothèques dans la littérature.; American.; LITERARY CRITICISM.; Books and reading; Libraries; Libraries in literature; Electronic books.; Criticism, interpretation, etc.